Biodegradation of chlorpyrifos by Pseudomonas sp. in a continuous packed bed bioreactor - Yadav M.; Srivastva N.; Singh R.S.; Upadhyay S.N.; Dubey S.K. (My University, 2025)
Biodegradation of chlorpyrifos (CP) by Pseudomonas (Iso 1) sp. was investigated in batch as well as continuous bioreactors packed with polyurethane foam pieces. The optimum process parameters for the maximum removal of CP, determined through batch experiments, were found to be: inoculum level, 300×106CfumL-1; CP concentration, 500mgL-1; pH 7.5; temperature, 37°C and DO, 5.5mgL-1. The continuous packed bed bioreactor was operated at various flow rates (10-40mLh-1) under the optimum conditions. The steady state CP removal efficiency of more than 91% was observed up to the inlet load of 300mgL-1d-1. The bioreactor was sensitive to flow fluctuations but was able to recover its performance quickly and exhibited the normal plug-flow behavior. Accumulation of TCP (3,5,6-trichloro-2-pyridinol) affected the reactor performance. © 2014 Elsevier Ltd.